Side Effect Rates of Opioids in Equianalgesic Doses via Intravenous Patient-Controlled Analgesia: A Systematic Review and Network Meta-analysis. (October 2019) - Dinges, Hanns-Christian; Otto, Stephan; Stay, David K.; Bäumlein, Synke; Waldmann, Susanne; Kranke, Peter; Wulf, Hinnerk F.; Eberhart, Leopold H.
Abstract : BACKGROUND: Side effects of opioids used for the treatment of acute pain frequently limit their analgesic quality. Many studies have compared opioid side effects in patient-controlled analgesia (PCA), but it remains unclear whether there are specific side effect profiles that can be exploited when choosing an opioid for a patient. In this review, we wanted to determine the risk ratios (RRs) for the most common side effects when using different opioids for intravenous PCA in equianalgesic doses and rank the substances accordingly. METHODS: A search of MEDLINE, EMBASE, the Cochrane Library (CENTRAL), and Web of Science identified 63 randomized controlled trials comparing opioids under equianalgesic conditions. Inclusion criteria were comparable pain stimulus between groups, equal coanalgesic treatment, and comparable resulting pain scores. Quality of studies was assessed using the Cochrane risk of bias tool with 6 items. Frequentistic network meta-analysis was conducted with morphine as the comparator. This method not only summarizes all estimated effects from direct comparisons of different interventions but also allows for indirect comparisons between interventions that can be linked via the common comparator, in which case the indirect evidence can be used to enhance the precision of the direct comparisons. Primary end points of this study were RRs for nausea and vomiting, pruritus, and events of sedation, as well as mean differences for scores of sedation. Events of respiratory depression were counted. Secondary end point was patient satisfaction (mean difference). The study protocol was registered at PROSPERO (CRD42017062355). RESULTS: Sixteen opioid interventions were compared in the largest network (nausea and vomiting outcome) and 7 opioid interventions in the smallest network (sedation events outcome). Most interventions did not differ from morphine on the primary outcomes (side effects), with some exceptions. Buprenorphine had a significantly higher RR of nausea and vomiting, whereas fentanyl had a lower RR of nausea and vomiting. Nalbuphine, butorphanol, methadone, and pethidine/meperidine had a lower risk of pruritus. Respiratory depression was rare (22 of 2452 patients). Pethidine/meperidine, fentanyl, and oxymorphone caused significantly lower sedation scores. Tramadol caused significantly lower satisfaction scores, whereas oxycodone, alfentanil, remifentanil, fentanyl, and pethidine/meperidine caused significantly higher satisfaction scores. CONCLUSIONS: The opiate chosen for treatment most likely has little effect on the incidence of pruritus and nausea/vomiting, although considerable differences exist in terms of better and worse opioids in the presented rankings. Larger differences between drugs were observed with regard to sedation and patient satisfaction, and choosing the appropriate opioid may help to improve PCA in this regard.